Assessment of heart rate response to exercise and recovery during treadmill testing in arsenic‐exposed workers. Issue 5 (1st March 2017) - Karakulak, Ugur Nadir; Gunduzoz, Meside; Ayturk, Mehmet; Tek Ozturk, Mujgan; Tutkun, Engin; Yilmaz, Omer Hinc
Abstract : Background: Arsenic exposure is associated with various cardiovascular diseases. The aim of the present study was to assess cardiac autonomic function via heart rate response to exercise and recovery period of treadmill testing in arsenic‐exposed workers. Methods: Sixty‐five (65) occupationally arsenic‐exposed workers and 35 healthy controls were enrolled. Blood and urinary arsenic levels were analyzed and symptom limited maximal treadmill exercise test were performed. Chronotropic response to exercise including age‐predicted maximal heart rate (APMHR), heart rate reserve (HRreserve ), age‐predicted HRreserve (APHRreserve ) and adjusted HRreserve and 1st‐, 2nd‐and 3rd‐min heart rate recovery (HRR) indices were calculated. Results: Baseline clinical and echocardiographic parameters, exercise test duration, resting and maximal heart rate, peak exercise capacity, HRreserve, APMHR, APHRreserve, and adjusted HRreserve were found to be similar between groups. HRR1 (22.0 ± 4.3 vs. 24.3 ± 3.1 bpm, p  = .003) and HRR2 (43.2 ± 6.2 vs. 46.7 ± 6.4 bpm, p  = .012) were significantly lower in arsenic‐exposed workers compared to controls. Blood and urinary arsenic levels negatively correlated with HRR1 ( r  = −.477, p  < .001 and r  = −.438, p  < .001, respectively) and HRR2 ( r  = −.507, p  < .001 and r  = −.412, p  < .001 respectively). Conclusions: Arsenic‐exposed workers had lower HRR indices than normal subjects but chronotropic response were similar. Cardiac autonomic dysregulation may be one of the cardiovascular consequences of arsenic exposure.